The effects of acute high-intensity aerobic exercise on cognitive performance: A structured narrative review - Sudo, Mizuki; Costello, Joseph T.; McMorris, Terry; Ando, Soichi (Frontiers in Behavioral Neuroscience, 2022)
It is well established that acute moderate intensity exercise improves cognitive performance. However, the effects of acute high intensity aerobic exercise on cognitive performance has not been well characterized. In this review, we summarize the literature investigating the exercise-cognition interaction, specially focusing on high intensity aerobic exercise. We discuss methodological and physiological factors that potentially mediate cognitive performance in response to high intensity exercise. We propose that the effects of high intensity exercise on cognitive performance are primarily affected by timing of cognitive task (during vs. after exercise, and the time delay after exercise). In particular, cognitive performance is more likely to be impaired during high intensity exercise when both cognitive and physiological demands are high and completed simultaneously (i.e. the dual-task paradigm). The effects may also be affected by type of cognitive task, physical fitness, exercise mode/duration, and age. Second, we suggest that interactions between changes in regional cerebral blood flow, cerebral oxygenation, cerebral metabolism, neuromodulation by neurotransmitters/neurotrophic factors, and a variety of psychological factors are promising candidates that determine cognitive performance in response to acute high intensity exercise. The present review has implications for recreational, sporting, and occupational activities where high cognitive and physiological demands are required to be completed concurrently.